Development and characterization of an atorvastatin solid dispersion formulation using skimmed milk for improved oral bioavailability - Ankush Choudhary; Avtar C. Rana; Geeta Aggarwal; Virender Kumar; Foziyah Zakir (Elsevier, 2012)
Atorvastatin has low aqueous solubility resulting in low oral bioavailability (12%) and thus presents a challenge in formulating a suitable dosage form. To improve the aqueous solubility, a solid dispersion formulation of atorvastatin was prepared by lyophilization utilising skimmed milk as a carrier. Six different formulations were prepared with varying ratios of drug and carrier and the corresponding physical mixtures were also prepared. The formation of a solid dispersion formulation was confirmed by differential scanning calorimetry and X-ray diffraction studies. The optimum drug-to-carrier ratio of 1:9 enhanced solubility nearly 33-fold as compared to pure drug. In vitro drug release studies exhibited a cumulative release of 83.69% as compared to 22.7% for the pure drug. Additionally, scanning electron microscopy studies suggested the conversion of crystalline atorvastatin to an amorphous form. In a Triton-induced hyperlipidemia model, a 3-fold increase in the lipid lowering potential was obtained with the reformulated drug as compared to pure drug. These results suggest that solid dispersion of atorvastatin using skimmed milk as carrier is a promising approach for oral delivery of atorvastatin.